Principles of macroeconomics - Nellis, J. G.; Parker, David (Harlow : Financial Times Prentice Hall, 2004)
Provides comprehensive coverage of the core principles of macroeconomics and explains how these macroeconomic concepts relate to government policy-making and the implications for the business environment. This book presents the principles with respect to fiscal policy, monetary policy, supply-side policy, trade and exchange rate policies.
Includes index.
oif 27/04/15
Loan
Keywords: Macroeconomics; Macroeconomics - principles